IMAGE OF QUASICOMPONENTS BY PROXIMATELY CHAIN REFINABLE FUNCTIONS - Buklla, Abdulla (Matematichki Bilten, 2023)
Proximate chain refinable functions were defined in [1] as a coarser class of functions from proximate refinable maps. In this paper we investigate some properties of these functions, we show that proximately chain refinable functions maps quasicomponents to quasiocomponents if codomain is with open connected components and in the end we provide some counterexamples.